Oscillations of freezing front in external enclosures - Parfentjeva, Natalija; Samarin, Oleg; Paulauskaitė, Sabina (Journal of Civil Engineering and Management, 2003)
An approximate procedure is proposed for calculating of the temperature field in a one-layer wall under harmonic variations of the external air temperature with regard to phase transitions of moisture within the wall. The trend of the freezing front displacement within the wall is researched as time goes on depending on relative thermal stability of the wall material and average thermal lag of the freezing layer. The engineering formulae are obtained for quantitative estimation of the front displacement offering determination of the peak value of its waves and their time lag with respect to the external temperature oscillations. The estimation of accuracy of the proposed calculation procedure is carried out and the limits of its suitability are detected. It has been shown that the error of the procedure falls in the limits of initial data under the magnitudes of the air temperature and thermal properties of employed materials meeting with in practice if the freezing front lays beyond the bounds of the violent temperature oscillation layer. First Published Online: 26 Jul 2012